Analisis Postur Kerja Terhadap Desain Mesin Sangrai Kopi Berkapasitas 10 kg Menggunakan Metode REBA - Sholahuddin, Tantan; Prasetyo, Prasetyo; Ariffin, Devi Eka Septriyani (Politeknik Negeri Batam, 2023)
Poor posture can cause user discomfort, changing human posture. If the posture has changed, it can affect daily activities. This study conducted a posture analysis of the design of a coffee roaster with a capacity of 10 Kg using the REBA method. Visualization analysis was carried out using solidworks software. The analysis was carried out by dividing the body by the arm when using a roasting machine. Analysis of body parts including neck position, trunk position and leg position, analysis of the arm including the position of the upper arm, the position of the lower arm and the position of the wrist. The height of an adult is assumed to be 166 cm. The analysis results that the risk of using a roasting machine is in the medium category, namely, changes are needed to the design of the roasting machine so that the use of the machine can be more optimal. The design of roasting machine can be improved by increasing the height of the machine frame or positioning the machine on a higher place.